High Mechanical and Tribological Stability of an Elastic Ultrathin Overcoating Layer for Flexible Silver Nanowire Films. (11th February 2015) - Lee, Hanleem; Han, Guebum; Kim, Meeree; Ahn, Hyo‐sok; Lee, Hyoyoung
<x xml:space="preserve">Abstract</x> A novel, nanoscale, thickness‐controlled, elastic graphene oxide–polydiallyldimethylammonium chloride (GO‐PDDA) film using a layer‐by‐layer technique on silver nanowires and a flexible substrate is reported. Micro‐ and nanoscale wear and flexibility depending on the thickness and/or elastic nature of the overcoating layer demonstrate high mechanical stability with the PDDA inserted overcoating layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>